The Methodology of Takhrīj and Legal Inference on the Practice of Qunūt in the Fajr Prayer: A Comparative Study of Ibn Ḥajar and al-Zaylaʿī - Muhammad Ilham Alfaiz; Muhammad Al Mighwar; Engkos Kosasih; Irwan Abdurrohman; Tajul Arifin (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Qunut shubuh (the supplication recited in the dawn prayer) remains a debated issue in Islamic jurisprudence, and disagreement over its legal status stems from differences in how hadith scholars evaluate the traditions cited as evidence. This study aims to comparatively analyze the takhrij (hadith verification) methodology and legal reasoning (istinbath al-hukm) employed by Al-Zayla'i in Naṣb al-Rāyah and Ibn Hajar al-Asqalani in Talkhīṣ al-Ḥabīr regarding hadiths on qunut shubuh, while identifying the epistemological patterns underlying their differences. This research is a qualitative library-based study, with the two takhrij works serving as primary data, analyzed through content analysis for the takhrij dimension and a comparative-analytical (tahlili-muqaran) approach for the legal-reasoning dimension. The findings show that both works engage in critical evaluation of the hadith chains related to qunut shubuh, yet display different epistemological styles in handling the results of that evaluation. Al-Zayla'i adopts a dialectical-cumulative approach, gathering arguments from conflicting authorities without rendering a firm personal verdict, which produces an open and context-dependent legal conclusion leaning toward understanding qunut shubuh within the context of qunut nazilah (situational supplication). Ibn Hajar al-Asqalani, by contrast, adopts an evaluative-declarative approach, explicitly and directly grading the reliability of each chain, which results in a legal conclusion structured hierarchically according to the strength of the transmission. This study concludes that the distinction between the two works lies not in the presence or absence of critical evaluation, but in the epistemological style of managing its outcomes suggesting that the ongoing legal disagreement over qunut shubuh can be understood as the consequence of two distinct yet equally valid epistemological paradigms within the tradition of Hadith Sciences.